2019
DOI: 10.34133/2019/3018568
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Printable Flexible and Stretchable Tactile Sensors

Abstract: Flexible and stretchable tactile sensors that are printable, nonplanar, and dynamically morphing are emerging to enable proprioceptive interactions with the unstructured surrounding environment. Owing to its varied range of applications in the field of wearable electronics, soft robotics, human-machine interaction, and biomedical devices, it is required of these sensors to be flexible and stretchable conforming to the arbitrary surfaces of their stiff counterparts. The challenges in maintaining the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 247 publications
0
68
0
Order By: Relevance
“…Solution‐processable printing technologies are very attractive for the realization of human interactive and highly compliant devices as they are simple, cost‐efficient and adaptable to various materials at freely defined layouts for functional elements. [ 14–17 ] Recent reports on printed electronics reveal the possibility to prepare also stretchable printed sensors of mechanical properties (strain, force, pressure, and bending), [ 18–21 ] which are relevant for on‐skin applications in human‐interactive systems, artificial intelligence, advanced prosthetics, and humanoid robots.…”
Section: Figurementioning
confidence: 99%
“…Solution‐processable printing technologies are very attractive for the realization of human interactive and highly compliant devices as they are simple, cost‐efficient and adaptable to various materials at freely defined layouts for functional elements. [ 14–17 ] Recent reports on printed electronics reveal the possibility to prepare also stretchable printed sensors of mechanical properties (strain, force, pressure, and bending), [ 18–21 ] which are relevant for on‐skin applications in human‐interactive systems, artificial intelligence, advanced prosthetics, and humanoid robots.…”
Section: Figurementioning
confidence: 99%
“…The technology to build the components for such a compliant multilayer system is partially available today. Currently, self-healing foils (Hönes et al, 2017 ), flexible sensors, and electronic circuits (Lu and Kim, 2014 ; Majidi, 2018 ; Kumar et al, 2019 ), solar batteries (Zhong et al, 2017 ), and, as shown above, smart actuators can be produced using, for example, multiphoton lithography (Malinauskas et al, 2009 ; Vaezi et al, 2013 ; Meza et al, 2014 , 2015 ), wafer technology (Kim et al, 2012 ; Segev-Bar and Haick, 2013 ), spray coating (Kent et al, 2020 ), and 3D and 4D printing (Kumar et al, 2019 ; Ma et al, 2019 ). Nevertheless, one challenge that remains open is the combination of all these components into one multi-materials system.…”
Section: Envisioning a True Avft As An Inspiration For Living Adaptivmentioning
confidence: 99%
“…These systems were made possible by utilizing various smart and partially soft materials as actuators, such as liquid crystal elastomers (LCEs) (Wani et al, 2017 ), shape memory alloys (SMAs) (Kim et al, 2013 ), and polymers (Mather et al, 2009 ; Behl et al, 2013 ; Meng and Li, 2013 ; Besse et al, 2017 ), electroactive polymers (e.g., DEA, Pelrine et al, 2000 ; Wang et al, 2019 , and IPMC, Shahinpoor, 2011 ), and materials with thermal (Behl et al, 2013 ), and humidity responsiveness such as hydrogel (Athas et al, 2016 ). The newest systems are capable not only of soft actuation but also of “soft sensing” by utilizing soft materials such as conductive elastomers or silicones and/or soft and flexible channels filled with liquid metals (e.g., EGaIn, consisting of a mixture of gallium, indium, and tin) forming soft sensors (Kumar et al, 2019 ). Materials systems are also available, functioning as stretchable electroluminescent skin; these are able to emit light actively, sense deformation, and withstand surface expansion of over 600% (Larson et al, 2016 ; Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…PDMS is a transparent, biocompatible, gas-permeable, and moldable (submicron resolution) elastomer that finds applications in microfluidics, 7 organ-on-a-chip, 8 membranes, 9 tissue engineering, 10 soft robotics, 11 and flexible electronics, 12 among others. Traditionally, PDMS structures such as microfluidic devices have been fabricated using soft lithography.…”
Section: Introductionmentioning
confidence: 99%